Intravelar veloplasty: A review - Rajshree Jayarajan; Anantharajan Natarajan; Ravindranathan Nagamuttu (Wolters Kluwer Medknow Publications, 2018)
Good speech is the ultimate aim in palate repair. Muscle function has to be optimum for the palate to be able to move to provide this goal. The fact that there has been a multitude of techniques of palatal repair indicates that none has been able to attain the intended objective. The method of intravelar veloplasty as a funtional technique has been the one that has gained wide acceptance all over the world. Use of magnification loops and microscope and better understanding of the cleft anatomy has helped to further refine the technique. This review aims at evaluating the outcome of this technique and its various modifications and complications. Literature search was performed in PubMed, Embase and Lilacs Bireme using the terms 'intravelar veloplasty', 'cleft palate repair', and radical muscle dissection'. No restriction were placed with regards to date of publication or language. Abstracts of the articles were assessed and the selected articles were reviewed in full by the authors. There is a striking diversity in the extent of muscle dissection between cleft surgeons. The evidence from the studies available showed better speech outcomes and velopharyngeal competence with radical intravelar veloplasty with varying complication rates. Uniformity in defining the degree of dissection of muscle by using a classification and standardised methods of outcome measurements are to be used in future studies to provide high quality evidence to guide decisions.